Pengaruh Penerapan Blended Learning Flex Model Terhadap Hasil Belajar Menulis Teks Prosedur Siswa Kelas IV di UPT SPF SDN Mamajang I Kota Makassar - Rezky Ayu Ariani; Sulfasyah Sulfasyah; Anin Asnidar (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
This research aims to see how much influence results from learning using the Blended learning flex model system on student learning outcomes and their role in the learning process, especially on the material of writing procedural texts. In this study, a One-Group Pretest-Posttest Design was used. One-Group Pretest-Posttest Design is a type of Pre-Experimental Design research. Data collection techniques use exams/tests and documentation. The population and sample size of this research are all class IV students at UPT SPF SDN Mamajang I, Makassar city, totaling 25 students. The results of this research are the pretest posttest which has been tested on students, and the results of hypothesis testing from this research are tcount = 11.0227 with ttable= 2.064, then Ho is rejected and H¹ is accepted. By rejecting